Impact of IFRS 9 in Light of Uncertainty Caused by Corona Pandemic - Rashwan, Abdul Rahman Mohammed; Shaqfa , Khalil Ibrahim (Jordan Journal of Business Administration, 2022)
This study aimed to highlight the impact of the application of the International Financial Instrumentation Standard (IFRS 9) in light of the uncertainty caused by the Corona pandemic. The results of the study concluded that IFRS 9 contributes to determining the expected credit losses that need to be recognized under the Corona pandemic in Palestinian banks listed in the Palestine Stock Exchange and that Palestinian banks listed in the Palestine Stock Exchange are working to prove the expected credit losses of financial instruments when credit risk increases in accordance with the requirements of the International Accounting Standard (IFRS 9). The researchers recommended that Palestinian banks listed in the Palestine Stock Exchange should further disclose financial instruments and estimate their financial impact in accordance with the requirements of the International Accounting Standard (IFRS 9) in case of uncertainty as a result of the Corona pandemic.